ANALISIS CURAH HUJAN UNTUK IRIGASI SEKUNDER DESA UNGGA KECAMATAN PRAYA BARAT KABUPATEN LOMBOK TENGAH - ROBINSIUS KARABA LUDJI; MUHAMAD YAMIN; NI MADE NIA BUNGA SURYA DEWI (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2023)
The purpose of this study was to determine the amount of discharge in the Ungga secondary canal irrigation network and to determine the K factor in the Ungga irrigation area. This type of research is a descriptive study to determine the performance of the Ungga secondary canal in the Batujai Dam, Central Lombok Regency. The results showed that the availability of water in Ungga irrigation starting from the preparatory period for processing water needs for plants was sufficient, the availability of water for October in the 2nd growing season was 18,400 l/s, while the need for paddy fields was 11.96 l/s, and still there is water availability of 1,538 l/s. Based on the results of the analysis of the K factor of 1,538 lit/sec, it means that the K factor in the Ungga irrigation secondary channel has met the irrigation planning standards (sufficient). The discharge (Q) on the main canal (intake) of the Batujai dam is sufficient.